2014
DOI: 10.3389/fpsyg.2014.01448
|View full text |Cite
|
Sign up to set email alerts
|

READING and FEELING: the effects of a literature-based intervention designed to increase emotional competence in second and third graders

Abstract: Emotional competence has an important influence on development in school. We hypothesized that reading and discussing children’s books with emotional content increases children’s emotional competence. To examine this assumption, we developed a literature-based intervention, named READING and FEELING, and tested it on 104 second and third graders in their after-school care center. Children who attended the same care center but did not participate in the emotion-centered literary program formed the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 52 publications
4
38
0
3
Order By: Relevance
“…All four young adults are experts in technology and learn in autodidactic way, but they show social and emotional deficits. Kumschick and collaborators highlighted the importance of emotional competence as an ability that is teachable and learnable [28]. We believe that the use of software that focuses on social and emotional relationships, such as "The Transporters", could help children with ASD improve their social competence [29].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…All four young adults are experts in technology and learn in autodidactic way, but they show social and emotional deficits. Kumschick and collaborators highlighted the importance of emotional competence as an ability that is teachable and learnable [28]. We believe that the use of software that focuses on social and emotional relationships, such as "The Transporters", could help children with ASD improve their social competence [29].…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies showed that children with a high level of emotional competence are more successful at interacting with their peer group [28,31,32]. On the contrary, children with a low level of emotional knowledge are often rejected by peers and can develop social anxiety and behaviour problems [28,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B. Kumschick et al, 2014) kann somit der Verbesserung sowohl sprachlicher als auch emotionaler Kompetenzen dienen.…”
Section: Diskussionunclassified